Pemilihan gaya belajar SMAN 1 Kota Pinang - Alfi Khairi Siregar; Dahniar Fitri (ARKA INSTITUTE, 2022)
This research highlights the importance of learning style selection for learners in an educational context, as an adaptation step towards active learning strategies that include searching and experimenting with learning approaches according to each individual's preferences. Learning style is a combination of how a person absorbs, organizes and processes information. Due to the different types of learning styles of each learner, this research focuses on understanding and applying students' learning styles based on individual psychology. The main objective is to provide teaching guidelines that suit different types of learning styles, while exploring the characteristics of students based on the dominance of their learning styles. Through this approach, the research seeks to improve learning effectiveness by considering the diversity of students' learning styles. Qualitative methods were used with data collection through interviews and questionnaire distribution. The survey results show that the average student at SMAN 1 Kota Pinang prefers Auditory learning methods, such as lectures, discussions, questions and answers, oral lectures, and listening to teachers provide information, compared to the visual and kinestic types.